Synthesis and characterization of CoFe2O4/BNT-BT0.08 core–shell nanotubes by a template based sol-gel method. Issue 9 (15th June 2018) - Cernea, Marin; Vasile, B.S.; Surdu, V.A.; Trusca, R.; Craciun, F.; Galassi, C.
Abstract: In this work we report on a new 1-1 composite coaxial nanostructure containing nanotubes of CoFe2 O4 and BNT-BT0.08 prepared by a template-based fabrication technique using the sol-gel chemistry. In this regard, CoFe2 O4 /BNT-BT0.08 core-shell nanotubes were prepared using a polycarbonate membrane template and sols precursors of CoFe2 O4 and BNT-BT0.08 . The deposition of nanotubes was performed by pore wetting of the porous membranes via capillary action and subsequent pyrolysis. The studies with scanning electron microscopy and transmission electron microscopy (TEM) revealed that the composite material is characterized by the 1-D tubular structure. Analysis by X-ray diffraction, high-resolution TEM imaging and selected-area electron diffraction pattern demonstrated that the synthetic composite nanotube CoFe2 O4 /BNT-BT0.08 has crystalline structure with cubic CoFe2 O4 and rhombohedral BNT-BT0.08 phases. CoFe2 O4 /BNT-BT0.08 coaxial nanotubes show dielectric properties, piezoelectric and ferromagnetic behavior.